Shielding assessment of the IAMI facility. (December 2020) - Liu, Z.; Trudel, A.; Augusto, R.S.; Buckley, K.
Abstract: The Institute for Advanced Medical Isotopes (IAMI) is TRIUMF's new facility dedicated to the research and production of medical isotopes. This work details the shielding requirements and radiological studies performed during the facility design. The initial design was based on the existing TR30-2 machine at TRIUMF, and then refined using Monte Carlo (MC) simulations. These calculations were performed with the MC particle transport and interaction code FLUKA, in several iterations, until occupancy and dosimetry requirements were met. The simulation results here documented, besides validating the shielding design, were also used to reduce materials' cost, optimize services' location as well as in the decommission study. Highlights: A new facility for large-scale medical isotope production at TRIUMF. Monte Carlo FLUKA simulations for shielding design optimization. IAMI dosimetry assessment and shielding validation.